THE SYMBOLIC MEANING OF JAVANESE KERIS’ PATRA ORNAMENT USING ETHNOLINGUISTIC APPROACH - Ana Nugrahaini Izzati; Mulyana Mulyana (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2020)
The Symbolic Meaning of Javanese Keris’ Patra Ornament using Ethnolinguistic ApproachAbstract: This study aimed to describe and to know the terms and symbolic meanings of Javanese keris’ patra ornaments. The meaning is not only lexical but also cultural; meaning which is associated with the civilization prevailing in that society. This research is a descriptive study using ethnolinguistic approach. Ethnolinguistic approach is used to uncover the meaning of the term patra deder which is related to local culture. The results of this study indicated that the patra ornament of Javanese keris has certain terms in each part. The meaning contained in the patra deder of Javanese keris is related to human life. It means that religious support, behaving politely and not arrogant, respecting each other, being responsible, obeying the prevailing norms and having positive thought are substantial in human life.Keywords: Symbolic meaning, Patra of Javanese keris, Ethnolinguistic MAKNA SIMBOLIS ISTILAH ORNAMEN PATRA KERIS JAWA DENGAN PENDEKATAN ETNOLINGUISTIK Abstrak: Penelitian ini bertujuan untuk menjelaskan dan memahami istilah pada ornamen patra keris Jawa dan makna simbolis yang terkandung di dalamnya. Makna tersebut tidak hanya makna leksikal saja, tetapi juga mengandung makna kultural yaitu makna yang dihubungkan dengan peradaban yang berlaku di masyarakat tersebut. Penelitian ini merupakan penelitian deskriptif dengan menggunakan pendekatan etnolinguistik. Pendekatan etnolinguistik adalah menguak makna istilah pada patra deder yang dihubungan dengan kultur kebudayaan setempat. Hasil penelitian ini menunjukkan bahwa ornamen patra keris mempunyai istilah-istilah tertentu pada setiap bagiannya. Makna yang terkandung di dalam patra deder keris yaitu berhubungan dengan kehidupan manusia. Sebagai manusia harus mempunyai penopang agama dan dalam bertingkah laku harus sopan, tidak sombong, saling menghargai sesama, tanggung jawab, mentaati norma yang berlaku, dan selalu berfikir positif.Kata kunci: Makna simbolis, Patra keris Jawa, Etnolinguistik